Income and Cost Structure of Paddy Farming and Minapaddy Farming on Tidal Land in Sungai Rebo Village, Banyuasin Regency: PENDAPATAN DAN STRUKTUR BIAYA USAHATANI PADI DAN MINA PADI PADA LAHAN PASANG SURUT DI DESA SUNGAI REBO KABUPATEN BANYUASIN - Merlita Fidiansari, Rossi; Purbiyanti, Erni (Sriwijaya Journal of Agribusiness and Biometrics in Agriculture Research, 2024)
The low productivity of tidal rice fields causes the rice fields to always be inundated. One way to increase the productivity and income of rice farmers in tidal land is to implement the rice-fish system. The objectives of this study are: (1) To analyze the income and cost structure of tidal rice farming and rice-fish farming in Dusun III Talang Andong, Banyuasin Regency; (2) To describe the obstacles for tidal rice farmers switching to rice-fish farming in Dusun III Talang Andong, Banyuasin Regency. The location selection was carried out intentionally (purposive). The sampling method was a simple random sampling method for rice farmers and a census method for rice-fish farmers. The cost structure was analyzed using the percentage proportion of each cost component to the total cost. The percentage proportion of fixed costs for rice farming was 30.84% ​​and rice-fish farming was 14.13%. While the percentage proportion of variable costs for rice farming was 69.16% and rice-fish farming was 85.87%. The income of mina padi farming is higher, which is Rp45,733,333/Ha/MT, while the income of rice farming is only Rp6,508,942/Ha/MT. With the obstacles faced by rice farmers to switch to the mina padi system, namely the high cost of building the mina padi system and production costs, in addition, most rice farmers in Dusun III Talang Andong still rent the rice fields they work on and the cost structure of rice farming is still dominated by labor wages and land rent so that there is a lack of allocation for purchasing production inputs.